Mirizzi syndrome grades III and IV: surgical treatment - REVERDITO,RONALD (2016)
ABSTRACT Objective : to evaluate the epidemiology and outcomes of surgical treatment of patients with Mirizzi Syndrome (MS) grades III and IV, the most advanced according to Csendes classification. Methods : we conducted a retrospective, cross-sectional study by reviewing records of thirteen patients with grades III and IV MS operated from December 2001 to September 2013, among the 3,691 cholecystectomies performed in the period. Results : the incidence of MS was 0.6% (23 cases) and grades III and IV amounted to 0.35% of this number. There was a predominance of type IV (12 cases). The preoperative diagnosis was possible in 53.8% of cases. The preferred approach was biliary-digestive derivation (10 cases), and "T" tube drainage with suture of the bile duct was the choice in three special occasions. Three patients had biliary fistula resolved with clinical management, and one coliperitoneum case required reoperation. In the outpatient follow-up of patients who underwent biliodigestive anastomosis (eight), 50% are asymptomatic, 25% had anastomotic stricture and 25% lost follow-up. The mean follow-up was 41.8 months. Conclusion : MS in advanced degrees has low incidence, preoperative diagnosis in only half of cases, and has the biliodigestive anastomosis as the best conduct, but not without morbidity.